PENGARUH LIKUIDITAS, SOLVABILITAS DAN PERPUTARAN AKTIVA TERHADAP PROFITABILITAS PADA PERUSAHAAN LEADER SUPERMARKET DI DILI TIMOR-LESTE - Freitas Ximenes, Marcelina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017DO - 10.24843/EEB.2017.v06.i08.p09, 2017)
The main objective of the company is to maximize wealth for shareholders. One way to achieve this goal is to improve the profitability of the company. All the company's resources should be utilized as much as possible in order to obtain profitability. Liquidity, solvency and asset turnover are part of the resource which can have a durect impact on corporate profits. In  improving the efficiency of the company to generate the expected profit, Investor can see from the side effects of ratios of the company on profitability. The more efficient ratios used by the company, the higher profitability can be achieved. This study aimed to determine the effect of the policy of liquidity, solvability and asset turnover on profitability in the campany Supermarket Leader in Dili Timor-Leste in 2009 - 2013 period. This research was conducted in Leader Supermarket, and data used in this study were the financial statements of the balance sheet and income statement for 5 years from 2009 - 2013. The data  analysis technique used was the technique of multiple linear regression analysis to test the effect of independent variables (Liquidity, Solvency of turnover Assets ratio) on the dependent variable (profitability). The results showed that 1) Liquidity had no significant positive effect on profitability; 2) Solvaability had no negatively significant effect on profitability; 3) Turnover assets had positive or significant effect on profitability. 4) Liquidity, solvability, and Asset turnover partially had a  significant effect on profitability. Profitability of the company demonstrates excellences in business competition where the  is higher the level of profitability of the company's performance the better. Working capital policcy is badly needed to achieve a competitive advantage so that the potential investor who want to invest in the company Supermarket Leader in Timor-Leste should consider variable of working capital those providing high profitability.